Cereblon-recruiting proteolysis targeting chimeras (PROTACs) can determine the selective degradation of HDAC1 over HDAC3 - Pavan, Aline R. [UNESP]; Smalley, Joshua P.; Patel, Urvashi; Pytel, Wiktoria A.; dos Santos, Jean Leandro [UNESP]; Cowley, Shaun M.; Schwabe, John W. R.; Hodgkinson, James T. (Royal Society of Chemistry (RSC), 2024)
Histone deacetylase (HDAC) enzymes 1-3 exist in several corepressor complexes and are viable drug targets. To date, proteolysis targeting chimeras (PROTACs) designed to target HDAC1-3 typically exhibit the selective degradation of HDAC3. Herein, we report cereblon-recruiting PROTACs that degrade HDAC1 with selectivity over HDAC3.